(untitled) (Texas Journal of Engineering and Technology, 2026)
This article analyzes the pedagogical significance of ideas related to labor education and career choice in the spiritual heritage of Eastern scholars. The study examines the views of Abu Nasr Forobiy, Abu Rayhon Beruniy, Abu Ali ibn Sino, and Alisher Navoiy, highlighting their perspectives on labor, professional skills, and personal development. The article reveals the role of labor as a means of achieving personal maturity, its importance in social development, and its close connection with moral education. It also substantiates that labor education contributes to the formation of essential personal qualities in students, such as responsibility, discipline, patience, and independence. The research findings indicate that the ideas of Eastern thinkers serve as an important methodological basis for guiding students toward professional orientation. It is emphasized that the integration of these ideas into the educational process can enhance students’ conscious career choice, as well as develop their diligence and independent thinking skills